In vitro kinetic release study, in vivo hydration and moisturizing effect of peel-off oil-in-water (O/W) nanoemulsion containing kojic monooleate for topical application - Nur Farzana Jaslina; Faujan, Nur Hana; Mohamad, Rosfarizan; Ashari, Siti Efliza (Wolters Kluwer - Medknow Publications and Media, 2022)
A derivative of kojic acid, kojic monooleate (KMO) contains tyrosinase inhibitor, and exhibits strong antioxidant activity makes it a good candidate to be incorporated into a formulation for topical application. A peel-off was chosen to ensure a better hydration effect and permeability of KMO into the skin. The objectives of this research were to analyze the kinetic release study of peel-off oil-in-water O/W nanoemulsion containing KMO and evaluate the moisturizing and hydration effect towards human volunteers. The peel-off formulation was developed by adding 27.61% w/w polyvinyl alcohol (PVA) and 1.05% w/w propylene glycol (PG). The study was performed by using Franz cell, tewameter and corneometer to analyze the release rate of KMO from peel-off O/W nanoemulsion, moisturizing, and hydration effect of formulation towards humans after 180 min of application, respectively. The final formulation has a pH of 4.74, conductivity of 7.47 ± 4.05 x 10-3 microS/cm, viscosity 0.1058 Pa·s and spreadability of 61.86 ± 1.71 g·cm/s. It also disports 79.99 ± 2.53 % released of KMO across the cellulose acetate membrane after 180 min of study time. The results of the hydration effect of the formulation towards human volunteers’ skin suggested that the peel-off O/W nanoemulsion containing KMO does increase the hydration of the skin by 12.33% due to the occlusive effect of KMO. In summary, this study presents new findings in kinetic release study, hydration and moisturizing effect of peel-off O/W nanoemulsion containing KMO for topical application.